2015
DOI: 10.15376/biores.10.3.4110-4125
|View full text |Cite
|
Sign up to set email alerts
|

Application of Photo, Peracetic Acid, and Combination Pre-treatments in Improving Totally Chlorine-Free Bleaching Selectivity

Abstract: The application of totally chlorine-free bleaching (TCF) is well recognised for its environmental compatibility. However, its application is restricted in comparison to a chlorine-based bleaching sequence. TCF bleaching produces pulp with relatively lower brightness and strength properties. Oxygen delignification (O-stage) is commonly used as a first bleaching stage; therefore its selectivity influences TCF bleaching performance. In this study, the selectivity of the O-stage and hydrogen peroxidereinforced O-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The obtained pulp activation using Paa results from the different chemistry of action of this compound with residual lignin in comparison to oxygen in the alkaline environment because it reacts not only with the phenolic rings of the lignin monomeric units but also with the non-phenolic residues of these units (Delagoutte et al 1999;Chong et al 2015). Moreover, it is reported that the treatment of kraft pulps with Paa effectively reduces the content of certain lignin-carbohydrate complexes (Jääskeläinen and Poppius-Levlin 1999) and hexenuronic acids contained in these pulps (Tavast et al 2011;Estaves et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained pulp activation using Paa results from the different chemistry of action of this compound with residual lignin in comparison to oxygen in the alkaline environment because it reacts not only with the phenolic rings of the lignin monomeric units but also with the non-phenolic residues of these units (Delagoutte et al 1999;Chong et al 2015). Moreover, it is reported that the treatment of kraft pulps with Paa effectively reduces the content of certain lignin-carbohydrate complexes (Jääskeläinen and Poppius-Levlin 1999) and hexenuronic acids contained in these pulps (Tavast et al 2011;Estaves et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This is because, in addition to the decrease in the residual lignin content of the pulp, the amount of lignin moieties having a degradation activation energy equal or even greater than the degradation process of polysaccharides increases (Karhunen et al 1994;Akim et al 2001). To delignify kraft pulps of low residual lignin content more selectively in bleaching, it has been proposed to use two-stage oxygen delignification of the pulps (Saldivia 2002;Johnson et al 2009) or to pre-treat them with substances that activate the residual lignin moieties of reduced susceptibility for delignification (Fossum and Marklund 1988), such as: performic acid (Hauque et al 2019); peracetic acid (Paa) (Poukka et al 1999;Turner et al 2004;Chong et al 2015;Zeinaly et al 2019;Sharma et al 2020); persulfuric acid (Allison and McGrouter 1995;Jafari et al 2014;Rizaluddin et al 2015); perphosphoric acid (Springer 1997); and salts of these acids (Springer and McSweeny 1993;Allison and McGrouter 1997;Zeinaly et al 2019;Bourchard et al 2000).…”
Section: Introductionmentioning
confidence: 99%